Keterampilan Komunikasi Mahasiswa Calon Guru Biologi Melalui Pembelajaran Microteaching: (Communication Skills of Biology Teacher Candidates Through Microteaching Learning) - Arwita, Widya; Hasruddin, Hasruddin; Ningsih, Widia; Mukra, Rizal; Rangkuty, Sailana Mira (BIODIK, 2025)
Communication skills are one of the essential abilities that teachers must possess to support their professional needs. Through good communication skills, teachers are able to convey teaching materials and various learning messages to students effectively. This research aims to determine the level of communication skills of prospective biology teacher students through microteaching. The type of this research is descriptive research. Data were collected from the entire population of fifth-semester students in the biology education program at FMIPA UNIMED in the Microteaching course. Communication skills consist of several aspects, including calmness, clarity of voice, clarity of material, and response to the audience. Based on the research results, it was found that in the aspect of calmness, a score of 72 was obtained, classified as competent; in the aspect of voice clarity, a score of 75 was obtained, classified as competent; in the aspect of material clarity, a score of 81 was obtained, classified as competent; and in the aspect of audience response, a score of 78 was obtained, classified as competent. Thus, overall, the communication skills received a score of 76, classified as competent. Abstrak. Keterampilan Komunikasi merupakan salah satu kemampuan yang wajib dimiliki guru guna menunjang kebutuhan profesionalismenya. Melalui kemampuan berkomunikasi yang baik guru mampu menyampaikan materi ajar dan berbagai pesan pembelajaran secara maksimal kepada siswa. Penelitian ini bertujuan untuk mengetahui tingkat keterampilan berkomunikasi mahasiswa calon guru biologi melalui pembelajaran mikroteahing. Tipe penelitian ini adalah penelitian deskriptif. Data dikumpulkan dengan populasi seluruh mahasiswa semester 5 program studi pendidikan biologi FMIPA UNIMED pada mata kuliah Mikroteaching. Kemampuan berkomunikasi terdiri dari beberapa aspek diantaranya ketenangan, kejelasan suara, kejelasan materi dan respon terhadap audiens. Berdasarkan hasil penelitian diketahui bahwa pada aspek ketenangan diperoleh nilai 72 yang diklasifikasikan sebagai cakap, pada aspek kejelasan suara diperoleh nilai 75 yang diklasifikasikan sebagai cakap, pada aspek kejelasan materi  diperoleh nilai 81 yang diklasifikasikan sebagai cakap, dan pada aspek respon terhadap audiens diperoleh nilai 78 yang diklasifikasikan sebagai cakap. Sehingga secara keseluruhan kemampuan berkomunikasi memperoleh nilai 76 yang diklasifikasikan sebagai cakap.